POTENSI NYAMPLUNG (Calophyllum inophyllum) DI PESISIR PANTAI TAMBAK RAWANG DESA GUNUNG SEMBILAN KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Amir, Faisal; Burhanuddin, Burhanuddin; Indrayani, Yuliati (JURNAL HUTAN LESTARI, 2019)
In 2012 a studi was conducted on the potential of Nyamplung in Ketapang and North Kayong Regencies, which stated that there were 219 trees of nyamplung potential in the coastal area of Tambak Rawang, North Kayong Regency. The next problem is how the nyamplung plant distribution conditions after seven years latter, whether there is a decrease or increase in population of nyamplung at Tambak Rawang coastal area, Sukadana District, Kayong Utara Regency. The purpose of this study is to examine the potential of nyamplung (Calophyllum inophyllum) in the coastal area of Tambak Rawang, Sukadana District, Kayong Utara Regency. This research was conducted at Tambak Rawang beach, Sukadana District, Kayong Utara Regency, West Kalimantan Province for approximately ± 1 month. Data collection techniques are carried out by the census of all nyamplung (C. inophyllum) trees found at the coastal area. Observations for seedling level were conducted by making 2 x 2 m plots placed by purposive sampling or deliberately at locations where there were many nyamplung seedlings at the observation site. Observation results show that there were 238 nyamplung trees found at the Tambak Rawang coastal area. The average number of primary, secondary and tertiary branches in the nyamplung tree are ± 5.18, ± 36.29 and ± 424.29 branches, respectively. Production of the weight of fruit in each tree is  ± 5.827 tons per fruit season. The number of nyamplung tree seedlings was found 6771 seedlings around the bottom of the nyamplung tree.Keyword : Coastal area, Kayong Utara, nyamplung (Callophyllum inophyllum), potency